Can we improve pollen season definitions by using the symptom load index in addition to pollen counts?. (September 2015) - Bastl, Katharina; Kmenta, Maximilian; Geller-Bernstein, Carmi; Berger, Uwe; Jäger, Siegfried
Abstract: Airborne pollen measurements are the foundation of aerobiological research and provide essential raw data for various disciplines. Pollen itself should be considered a relevant factor in air quality. Symptom data shed light on the relationship of pollen allergy and pollination. The aim of this study is to assess the spatial variation of local, regional and national symptom datasets. Ten pollen season definitions are used to calculate the symptom load index for the birch and grass pollen seasons (2013–2014) in Austria. (1) Local, (2) regional and (3) national symptom datasets are used to examine spatial variations and a consistent pattern was found. In conclusion, national datasets are suitable for first insights where no sufficient local or regional dataset is available and season definitions based on percentages provide a practical solution, as they can be applied in regions with different pollen loads and produce more constant results. Highlights: The definition of the pollen season has an impact on the calculated symptom load. Pollen season definitions based on percentages of total pollen are a practical solution. The symptom load index is a robust tool to assess the allergy burden in a population. Local, regional and national burdens of pollen allergy sufferers are comparable. Abstract : The symptom load index is a robust tool to assess the allergy burden in a population. Local, regional and national burdens of pollen allergy sufferers are comparable.